2022
DOI: 10.3390/molecules27186134
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Chemical Composition, Bioactive Substance, Gas Production, and Rumen Fermentation Parameters of Four Types of Distiller’s Grains

Abstract: Distiller’s grain is rich in natural active ingredients and can be used as an excellent antioxidant feed for goats. The current study aimed to assess the feeding value of four different types of distiller’s grains with an in vitro gas production trial. The chemical composition, total phenols, total anthocyanins, dry matter degradability, methane, hydrogen, and rumen fermentation parameters were evaluated. The results indicated that red distiller’s grain and glutinous rice distiller’s grain had higher (p < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In the present study, M6 contained the lowest level of GP during the entire incubation period, probably because it contained higher levels of polyphenol compounds such as apigenin, genistin, vitexin, isovitexin, and aloe emodin, as well as higher total polyphenols; however, this assumption needs further validation. Nevertheless, our results are consistent those of with Lu et al [18], who showed that high-polyphenol feed could inhibit methane production, and result in a low level of GP, in in vitro ruminal fluid incubation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, M6 contained the lowest level of GP during the entire incubation period, probably because it contained higher levels of polyphenol compounds such as apigenin, genistin, vitexin, isovitexin, and aloe emodin, as well as higher total polyphenols; however, this assumption needs further validation. Nevertheless, our results are consistent those of with Lu et al [18], who showed that high-polyphenol feed could inhibit methane production, and result in a low level of GP, in in vitro ruminal fluid incubation.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, sorghum stalk, as a cheap crop, may be an ideal source of unconventional feed for ruminants. However, previous studies have analyzed total polyphenols using spectrophotometric methods; as a result, the subgroups of polyphenols are not yet fully understood [17,18], and the application of sorghum stalk remains restricted to some extent. Interestingly, polyphenol subgroups in sorghum stalks may be detected by high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS) technology.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics including Lactobacillus and Bifidobacterium may scavenge reactive oxygen species via their antioxidant system [27], enzyme-producing activity, and the regulation of host gastrointestinal microbiota to regulate the redox status of the host [12]. In addition, studies have proven that DG is rich in polyphenolic compounds with strong bioactive properties, including total phenols and anthocyanins [28], and exhibits strong antioxidant activities [29]. Li et al [30] found that dried distillers' grains containing solubles (DDGS) increased the activities of CAT, T-SOD, and GSH-Px in the serum of dairy cows.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the vast majority of distiller's grains processing technologies are based on the resource reuse of distiller's grains. A large number of studies have reported different resource utilization pathways of distiller's grains, as shown in Figure 1, including measures such as producing fuel, feed, and organic fertilizer from distiller's grains [1][2][3][4][5][6] . This article aims to summarize the current application status and development potential of distiller's grains in energy, agriculture, and food industries, as well as the opportunities and challenges for their application and development.…”
Section: Introductionmentioning
confidence: 99%